(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Start in the classrooms mother language lessons students speech competencies in formation the most important stage is considered. Because this at the age of children the language to study very open, speech main laws to occupy ready Therefore, start in the classrooms speech competencies effective develop education process quality determinant main from factors one is considered.